Breaking Out the Traditional Polymerization: Tailoring the Shape, Structure, and Optical Properties of Polydopamine by Using CdTe Quantum Dots. Issue 13 (28th May 2019) - Ortega, Greter A.; Zuaznabar‐Gardona, Julio C.; Mendoza‐León, Héctor F.; Cayetano‐Castro, Nicolás; Acevedo‐Peña, Próspero; Reguera, Edilso
Abstract: The potential applications of shape‐controlled polymeric nanostructures demand well‐defined methods to create tailored shapes. On the other hand, polydopamine (PDA) is a novel polymer promising a variety of innovative applications in many different areas. Since there is no consensus on the pathways involved in the mechanism of formation of PDA, the control of the final morphologies of PDA nanostructures is a challenging task. Herein, it is demonstrated for the first time, how CdTe quantum dots (CdTe QDs) can be used to control the final shape of polymeric structures, in particular, PDA particles. Oxidative self‐polymerization of dopamine is performed in the presence of CdTe QDs, which triggers the formation of blue‐colored rod‐like PDA particles. Scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV‐Vis, Fourier transform infrared (FT‐IR) and Raman spectroscopies, and electrochemical techniques are employed to characterize the structural features of the rod‐like PDA particles. Herein, CdTe QDs modulate the oxidative polymerization of dopamine by the supramolecular assembly of PDA building blocks by π–π and hydrogen bonding interactions, coordination with cadmium ions, and electron transfer processes. The results illustrated here describe a new strategy to manipulate the morphology of PDA nanostructures leading to novel optical properties, opening new applications, and shedding light on the complex mechanism of PDA formation. Abstract : Oxidative self‐polymerization of dopamine is performed in the presence of CdTe quantum dots (QDs), which triggers the formation of blue‐colored rod‐like polydopamine (PDA) particles during a controlled shape growth. Herein, QDs modulate the supramolecular assembly of PDA building blocks by π–π and hydrogen bonding interactions, coordination with cadmium ions, and electron transfer processes.